ANALISIS KEMAMPUAN KREATIVITAS SISWA SMA DALAM MEMECAHKAN MASALAH FISIKA - Wulandari, Mashelin; Rodriguez , Edna Virginia; Afrianda, Sara (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2024)
teaching and learning process is an activity that involves various elements that interact with each other to achieve a goal, for example student creativity. This research aims to analyze the influence of students' creative abilities on their ability to solve physics problems. This research is qualitative research with a type of literature study. The data analyzed is secondary data obtained through research documents in reputable journals. The results of research data analysis show that there is a positive influence between student creativity on the ability to solve physics problems on the subject of physical optics in class XI-A Senior high school 3 Jombang students. This creative ability is one of the important abilities for students to have in order to achieve optimal learning outcomes. Novelty in this research is information regarding the influence of creativity on problem-solving abilities in physics subjects.